Sensitivity Study on the Influence of Parameterization Schemes in WRF-ARW Model on Short- and Medium-Range Precipitation Forecasts in the Central Andes of Peru - Moya-Álvarez A.S. (2018)
A sensitivity study of the performance of the Weather Research and Forecasting regional model (WRF, version 3.7) to the use of different microphysics, cumulus, and boundary layer parameterizations for short- and medium-term precipitation forecast is conducted in the Central Andes of Peru. Lin-Purdué, Thompson, and Morrison microphysics schemes were tested, as well as the Grell–Freitas, Grell 3d, and Betts–Miller–Janjic cumulus parameterizations.